Answer:
(x) =
![(2-x)/(x-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2jpmg7grw92bhl3gic3i6sk0ogzpdd3n4j.png)
Explanation:
Let y = f(x) and rearrange making x the subject
y =
( multiply both sides by (x + 1)
y(x + 1) = x + 2 ← distribute left side
yx + y = x + 2 ( subtract x from both sides )
yx - x + y = 2 ( subtract y from both sides )
yx - x = 2 - y ← factor out x on the left side
x(y - 1) = 2 - y ← divide both sides by (y - 1 )
x =
![(2-y)/(y-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z0arne9y9honj3t5kgt5x0gpygrqtw07ev.png)
Change y back into terms of x, thus
(x) =
![(2-x)/(x-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2jpmg7grw92bhl3gic3i6sk0ogzpdd3n4j.png)